Agroecologia, saber local e mercado: um estudo sobre a agricultura familiar de Poço Fundo, MG - Gonçalves, Alexandre (2003)
Organic food production is an activity that has been developed by family farmers in different regions of Brazil. The commercialization of organic products has some particularities. It is composed of different channels from those used by other food crops and a certifícation system. The production of organic food and its certifícation involves a network that includes specialized markets around the world. This production includes economic, environmental and social aspects. The present study seeks to comprehend how family farmers from Poço Fundo, Minas Gerais, organize for the production and commercialization of their products. To accomplish the goals a theoretical reference which interfaced geography, anthropology, sociology and economics, was necessary. The relations among family farmers, the geographical space of their occupation and the trade relations with the market were analyzed. Organic food production is a reaction to local reality changes caused by modem agriculture and the capitalism system on rural áreas. Organic production is very important to Poço Fundo. It involves political, ideological, environmental, cultural and economic aspects. The commercialization process construct borders that comes from power relations in the certifícation system. In this system producers has to adjust to procedures to participate in the market. On the other hand, producers construct strong groups based on the act of living in society. These groups are still based on environmental and knowledge reproduction.